Hypopigmented Mycosis Fungoides: A Clinicopathological Review of 32 Patients - Shi H; Jiang Y; Xu X; Zhang W; Song H; Wang X; Zeng X; Sun J; Chen H (Dove Medical Press, 2022)
Hao-ze Shi, Yi-qun Jiang, Xiu-lian Xu, Wei Zhang, Hao Song, Xiao-po Wang, Xue-si Zeng, Jian-fang Sun, Hao Chen Department of Pathology, Institute of Dermatology, Chinese Academy of Medical Sciences and Peking Union Medical College, Nanjing, 210042, People's Republic of ChinaCorrespondence: Hao Chen; Jian-fang Sun, Department of Pathology, Institute of Dermatology, Chinese Academy of Medical Sciences and Peking Union Medical College, Nanjing, 210042, Email ch76ch@163.com; fangmin5758@aliyun.comBackground: Hypopigmented mycosis fungoides (hMF) is gradually acknowledged by more dermatologists, yet a consensus regarding its characteristics is not reached. The profile of Chinese hMF patients has not been deeply reviewed previously. Our research may contribute to the understanding of hMF, especially the Chinese patients with Fitzpatrick phototypes of III and IV.Aim: To have a better understanding of hMF in terms of clinical, histopathological and immunohistochemical features in the Chinese population and to determine if there are differences between the Chinese population and other ethnic groups.Methods: We made a retrospective analysis of clinical, histopathological and immunohistochemical features of 32 hMF patients in our hospital from 2010 to 2020. These features were then summarized and compared with previous reports.Results: All patients belonged to Fitzpatrick phototypes of III or IV. Twenty-one male (65.63%) patients and 11 female (34.37%) patients were analyzed, and the male to female ratio was 1.9:1. The age at diagnosis of patients ranged from 4 to 39 years, and the average age at diagnosis of these patients was 18 years, the median age was 16.5. Back was the most frequent site (34.37%). The clinical and histological results of lesions had no distinctive points. Immunohistochemically, among these 32 patients, there were 30 patients whose information was complete, there was 19 patients (63.33%) who were CD8 positive lymphocytes predominance, 9 patients (30%) had CD8 and CD4 positive lymphocyte mixed infiltration, and other 2 patients (6.67%) had CD4 positive lymphocytes predominance. Partial loss of CD7 was only observed in 1 patient (3.33%). Nearly all patients adopted topical nitrogen mustard and topical steroid and most of them had an excellent prognosis.Conclusion: The clinical profiles of hMF in Chinese population shared differences with other ethnic groups, but its histopathological, immunohistochemical results and prognosis condition were resembled with other previous reports. Hence, more patients were needed to find the characteristics of hMF.Keywords: hypopigmented, mycosis fungoides, cutaneous, MF